Strength and deformation characteristics of cement treated soft Bangladesh clays - Md. Mokhlesur, Rahman, Prof.; Abu Taher, Md. Zillur Rabbi; Abu Siddique, Prof. (Institution of Engineers, Malaysia (IEM), 2012)
Link to publisher's homepage at http://www.myiem.org.my/